2023
DOI: 10.37233/trsped.2023.0136
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Self-Competence of Youths with Visual Impairment in the Expanded Core Curriculum Skills

Abstract: The purpose of this study was to evaluate the perceived self-competence of youths with visual impairment in Turkey in the Expanded Core Curriculum (ECC) areas. To examine how youths with visual impairment perceive their self-competence within the nine ECC areas, an ECC screening tool developed by the Iowa Department of Education was adapted into a five-point Likert-type scale (ranging from 1 = strongly disagree to 5 = strongly agree). Participants were 118 high school students with visual impairment across Tur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…In particular, since there is not any specialist curriculum framework designed specifically for learners with vision impairment to improve their independence skills in schools in Turkey (Akbayrak et al, 2023), such as the expanded core curriculum (ECC) in the United States (Sapp & Hatlen, 2010) or the curriculum framework for children and young people with vision impairment in the United Kingdom (CFVI) (Hewett et al, 2022), it may well be argued that there is limited educational support in schools in order for Turkish young people with vision impairment to 'develop agency to facilitate independent learning and social inclusion' (McLinden et al, 2020, p. 14). Unsurprisingly, a recent study, which investigated perceived self-competencies of young people with vision impairment relating to the ECC skills in Turkey, indicated that young people had notably lower levels of self-competence in a number of the ECC areas, including compensatory/ access and assistive technology skills (Akbayrak et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, since there is not any specialist curriculum framework designed specifically for learners with vision impairment to improve their independence skills in schools in Turkey (Akbayrak et al, 2023), such as the expanded core curriculum (ECC) in the United States (Sapp & Hatlen, 2010) or the curriculum framework for children and young people with vision impairment in the United Kingdom (CFVI) (Hewett et al, 2022), it may well be argued that there is limited educational support in schools in order for Turkish young people with vision impairment to 'develop agency to facilitate independent learning and social inclusion' (McLinden et al, 2020, p. 14). Unsurprisingly, a recent study, which investigated perceived self-competencies of young people with vision impairment relating to the ECC skills in Turkey, indicated that young people had notably lower levels of self-competence in a number of the ECC areas, including compensatory/ access and assistive technology skills (Akbayrak et al, 2023).…”
Section: Introductionmentioning
confidence: 99%